التنمية السياسية: النشأة و المفهوم - برقوق, عبد الرحمان; العيدي, صونيا (Sciences de l'Homme et de la Société, 2013)
يعتبر مفهوم التنمية السياسية من المفاهيم الصعب الإجماع حولها بتعريف جامع مانع، وذلك لاعتبارات عدة، و لعل أكثر ما يلفت انتباهنا منها أولا حداثته النسبية إذ تمخض علميا في أعقاب الحرب العالمية الثانية إثر توجه الإيديولوجيات العلمية للاهتمام بالمجتمعات الثالثية. و ثانيا هو أن المفهوم مركب من مصطلحين أو بالأحرى مفهومين. و لعل هذين الصعوبتين – على الأقل- يجعلانا نستوعب ما يمكن أن تثيره محاولات تعريف هذا المفهوم من إشكالات – صريحة و ضمنية – بين الطروحات الغربية و بين الطروحات العربية نتيجة خصوصيات بنية الشعوب و كذا أهدافها.     The concept of political development is considered one of the concepts that is difficult to agree upon through inclusive and comprehensive definition, this, for several considerations; and perhaps what draws more our attention is, first, its relative novelty, as it scientifically resulted, after the second world war, from the orientations of scientific ideologies that were concerned with tertiary communities, and secondly, that the concept is a composite of two concepts, or rather two notions. And perhaps these two difficulties – at least- makes us understand what can be raised, by attempts to define this concept, as problematics (explicit and explicit) between western propositions and arab propositions due to the specificities of structure of peoples as well as its goals.